Epilepsy in adult patients with tuberous sclerosis complex. (22nd March 2021) - Vignoli, Aglaia; La Briola, Francesca; Turner, Katherine; Peron, Angela; Vannicola, Chiara; Chiesa, Valentina; Zambrelli, Elena; Bruschi, Fabio; Viganò, Ilaria; Canevini, Maria Paola
Abstract: Objectives: Little is known about the evolution of epilepsy in individuals with tuberous sclerosis complex (TSC) in adulthood. This study aims at describing the characteristics of epilepsy in adult TSC patients attending a single multidisciplinary clinic. Materials and Methods: We collected data about epilepsy (age at onset, seizure types, history of infantile spasms (IS), epilepsy diagnosis and outcome), genetic and neuroradiological findings, cognitive outcome and psychiatric comorbidities. Results: Out of 257 adults with TSC, 183 (71.2%) had epilepsy: 121 (67.2%) were drug‐resistant; 59 (32.8%) seizure‐free, at a median age of 18 years. 22% of the seizure‐free patients (13/59) discontinued medication. Median age at seizure onset was 9 months. Seventy‐six patients (41.5%) had a history of IS. TSC2 pathogenic variants ( p  = 0.018), cortical tubers ( p  < 0.001) and subependymal nodules (SENs) ( p  < 0.001) were more frequent in those who developed epilepsy. Cognitive functioning was lower ( p  < 0.001) and psychiatric disorders more frequent ( p  = 0.001). We did not find significant differences regarding age, gender, mutation and tubers/SENs in seizure‐free vs drug‐resistant individuals. Intellectual disability ( p  < 0.001) and psychiatric disorders ( p  = 0.004) were more common among drug‐resistant patients. Conclusions: Epilepsy in TSC can be a lifelong disorder, but one‐third of individuals reach seizure freedom by early adulthood. In the long term, age at epilepsy onset has a crucial role in drug resistance and in developing intellectual disability, both in drug‐resistant and drug‐sensible patients. Patients with drug‐refractory seizures tend to develop psychiatric issues, which should be recognized and adequately treated.